Modified matched filter kernel for classification of hard exudate - Ladkat, Ajay S.; Patankar, Sanika S.; Kulkarni, Jayant V. (2016 International Conference on Inventive Computation Technologies (ICICT), 2016)
Diabetic Retinopathy is an abnormality of eye in which the retina of patient is affected due to an increasing amount of insulin in blood. The symptoms can distort or blur the patient's vision and thus lead blindness. For automatic detection of exudates we first have to differentiate intensity levels of exudate and non-exudate pixels. Matched filter is used for same. Tuning of matched filter is an important criteria which is presented in this paper. This paper contains how to tune and modify matched filter response for easily segmentation of Hard Exudates. It also contains graphical experimented results for different values of sigma and how accuracy of the algorithm varies with it. Experimentation gives 99.62% accuracy of classification of exudate - non-exudate pixels and subject level accuracy is found to be 93.75% in identifying the abnormal (with exudates) and normal (without exudates) images respectively.